The effect of financial stability, industrial conditions and external pressures on fraudulent financial statements in manufacturing companies listed on the indonesia stock exchange for the 2019-2020 period - Anisa Rizki Fitriastuti; Martina Khusnul Umami (Islamic Accounting Journal, 2021)
This study to examine financial stability, industrial conditions and external pressures and their effects on financial reports. Financial stability was tested using ACHANGE, industrial conditions were tested using RECEIVABLE, external pressure was tested using Debt To Asset (DTA), and fraudlent financial statments were test using EDAIT. This study uses secondary data quantitative methods. The population in this study are manufacturing companies listed on the IDX. The analysis technique used is multiple regression analysis which shows that financial stability and industrial conditions have a negative effect on financial statement fraud, while external pressure has a positive effect on financial statement fraud